Analisis Kesehatan dan Keselamatan Kerja Penggunaan Pestisida Menggunakan Metode ASNZS 4360:2004 dan Job Safety Analysys (JSA) - Putri Nur Hasanah; Saniatun Wilda; Natasya Shafira Putri Rahmat; Hilman Imadul Umam; Teguh Pambudi (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
ABSTRACT The use of pesticides in agricultural activities is still frequently carried out without adequate implementation of occupational safety and health (OSH) procedures, such as incomplete use of personal protective equipment (PPE) and unsafe mixing and spraying practices, which increases the risk of health problems and environmental contamination. Commonly reported health effects include skin irritation, dizziness, muscle pain, respiratory disorders, and musculoskeletal complaints. This study aims to analyze occupational safety and health risks associated with pesticide use among farmers by applying the AS/NZS 4360:2004 risk management method and Job Safety Analysis (JSA). The study employed a qualitative descriptive approach through interviews and direct observations of work activities, including equipment and material preparation, pesticide mixing, spraying, and sprayer tank cleaning. Risk assessment was conducted based on three indicators, namely exposure, probability, and consequence, to determine risk levels and identify appropriate control measures. The results indicate that the preparation stage of equipment and materials is the most critical, with back pain classified as a “Substantial” risk and swollen feet categorized as “Priority 3.” Other work stages were generally classified as “Acceptable,” although the potential for direct pesticide exposure remains a concern. Recommended risk control measures include consistent use of PPE, regular OSH training, and improvements in work procedures to reduce manual handling risks and chemical exposure, thereby supporting safer and more sustainable agricultural practices. Keywords : Occupational Health Risk, K3, Pesticide Use ABSTRAK Penggunaan pestisida dalam aktivitas pertanian masih banyak dilakukan tanpa penerapan prosedur keselamatan dan kesehatan kerja (K3) yang memadai, seperti ketidaklengkapan alat pelindung diri (APD) serta teknik pencampuran dan penyemprotan yang tidak aman, sehingga meningkatkan risiko gangguan kesehatan dan pencemaran lingkungan. Dampak kesehatan yang sering dilaporkan meliputi iritasi kulit, pusing, nyeri otot, gangguan pernapasan, dan keluhan muskuloskeletal. Penelitian ini bertujuan untuk menganalisis risiko K3 pada penggunaan pestisida oleh petani dengan menggunakan metode AS/NZS 4360:2004 dan Job Safety Analysis (JSA). Penelitian dilaksanakan dengan pendekatan deskriptif kualitatif melalui wawancara dan observasi langsung terhadap tahapan kerja yang meliputi persiapan alat dan bahan, pencampuran pestisida, penyemprotan, serta pencucian tangki semprot. Penilaian risiko dilakukan berdasarkan indikator exposure, probability, dan consequence untuk menentukan tingkat risiko serta kebutuhan pengendalian. Hasil analisis menunjukkan bahwa tahap persiapan alat dan bahan merupakan tahapan paling kritis, dengan risiko nyeri punggung berada pada kategori “Substantial” dan risiko kaki bengkak termasuk kategori “Priority 3.” Sementara itu, tahapan kerja lainnya umumnya berada pada kategori “Acceptable,” meskipun potensi paparan pestisida secara langsung tetap perlu diperhatikan. Upaya pengendalian yang direkomendasikan meliputi penggunaan APD secara konsisten, pelaksanaan pelatihan K3 secara berkala, serta perbaikan prosedur kerja untuk mengurangi risiko pengangkatan manual dan paparan bahan kimia, guna mendukung praktik pertanian yang lebih aman dan berkelanjutan Kata Kunci : Resiko Kesehatan Kerja, K3, Penggunaan Pestisida